Improving Students’ Reading Comprehension of Descriptive and Narrative Texts Through Canvas-Based Gamification - Desty Febria; Inne Dasilva Angel (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2026)
Reading comprehension is one of the essential skills in English language learning. However, many students still encounter difficulties in understanding vocabulary, identifying detailed information, and comprehending descriptive and narrative texts. This study aimed to improve students’ reading comprehension skills through the implementation of Canvas-based gamification. The study employed a Classroom Action Research (CAR) design involving 37 tenth-grade students at a public senior high school in Batam. The research was conducted in two cycles, consisting of planning, action, observation, and reflection stages. The gamification strategies implemented in Canvas included the use of points, interactive quizzes, and direct feedback to enhance students’ engagement and motivation in reading activities. Data were collected through reading comprehension tests, observation sheets, and field notes. The findings revealed a significant improvement in students’ reading comprehension skills. The mean score increased from 64.27 in Cycle I to 74.11 in Cycle II, representing a 15.31% improvement. In addition, the percentage of students categorized as Very Good increased from 8.11% to 51.35%. The observation results also indicated that students became more active, engaged, and motivated in reading activities through the integration of gamification features within the Canvas Learning Management System (LMS). Therefore, Canvas-based gamification can serve as an effective instructional strategy for improving students’ reading comprehension of descriptive and narrative texts in English language learning.